The effect of the strange link strategy on the achievement of geography among literary fifth-grade students - Kareem Sajit, Hatem (Journal of College of Education, 2021)
The research aims to know (the effect of the strange link strategy on the achievement of geography among literary fifth-grade students. To achieve the research goal, the researcher put the following null hypothesis:There is no statistically significant difference at a level of significance (0.05) between the average scores of the experimental group students who study the geography subject with the strange link strategy and the average scores of the control group students who study the same subject in the traditional way in the post achievement test, and the researcher used the experimental design with partial control (for the group The experimental and control group), and intentionally chose (Taha Al-Amin's high school) to be the field of research, and for the purpose of applying the experiment, the sample consisted of (60) students, by (30) students per group. The chronological age calculated in months, the parents ’academic achievement, and the geographical subject grades for the previous year, and the researcher used the antenna test to identify the statistical significance and after analyzing the results, it resulted in a statistically significant difference at the level of (0.05) between the average of the experimental group that was studied according to the surprising link strategy The average of the control group that was studied according to the traditional method of achievement in the geography subject.
Keywords: strategy (the strange link), achievement, geography course, literary fifth grade.